Dual circularly polarised omnidirectional antenna. Issue 6 (26th March 2019) - Wang, Ankang; Li, Xi; Yi, XiangJie; Yang, Lin; Zhao, Jiawei; Li, Aiqin
Abstract : A dual circularly polarised (CP) omnidirectional antenna is proposed. The antenna consists of an in‐phase current loop, a printed dipole and a feed network. The in‐phase current loop formed by zero‐phase‐shift line is placed orthogonally to the printed dipole to produce Eφ and Eθ components in the far‐field of antenna radiation. By adjusting the amplitude and phase of Eθ and Eφ, good CP characteristics can be formed. A simple and feasible 3 dB coupler can realise the switching between the left‐hand CP (LHCP) and right‐hand CP (RHCP) without additional complex feed structure. Furthermore, the structure of the parallel strip line to the microstrip can effectively eliminate the unbalanced current of the coaxial cable. Finally, the optimised antenna was processed and measured. The measured results show that the impedance bandwidth (| S 11 |<−10 dB) is 260 MHz (2320–2570 MHz) and 255 MHz (2340–2595 MHz) at two feed ports, respectively. It is worth mentioning that the antenna has a simple structure and a good omnidirectional CP radiation mode in the 2.45 GHz WLAN band.